2003
DOI: 10.1038/sj.ijo.0802325
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial hypothalamus lesions induce jejunal epithelial cell hyperplasia through an increase in gene expression of cyclooxygenase

Abstract: BACKGROUND:We demonstrated that ventromedial hypothalamus (VMH) lesions facilitate DNA synthesis, which reflects cell proliferation in abdominal organs, including the liver, pancreas, stomach, small intestine and large intestine, all of which are amply innervated by the vagal nerve. OBJECTIVE: To investigate which area DNA synthesis facilitates and what factors contribute to cell proliferation in the small intestine in VMH-lesioned rats. DESIGN: At 7 days after VMH lesions or sham operations, a segment of rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…4), which is consistent with results from previous studies of the digestive tract (26). It is likely that enhanced proliferation of the epithelial cells in the duodenal crypts results in duodenal villi elongation.…”
Section: Duodenumsupporting
confidence: 82%
“…4), which is consistent with results from previous studies of the digestive tract (26). It is likely that enhanced proliferation of the epithelial cells in the duodenal crypts results in duodenal villi elongation.…”
Section: Duodenumsupporting
confidence: 82%
“…Therefore, these effects may be involved in the resistance to ethanol-induced AGML in VMH-lesioned rats. On the other hand, we previously observed an increase in the gene expression of COX-1 and COX-2 in the jejunum of VMH-lesioned rats (Kageyama et al 2003), which should have the stimulatory effect on cell proliferation. Consequently, it is likely that these factors together contribute to the manifestation of resistance to ethanolinduced AGML.…”
Section: Discussionmentioning
confidence: 94%
“…To date, we have shown that both COX-1 and -2, but not EGF or TGF-α mRNA levels, are increased in the jejunal epithelial cells of VMH-lesioned rats (Kageyama et al 2003). Further study is required to identify what molecules contribute to the cell proliferation process in the gastric mucosa of these animals.…”
Section: Discussionmentioning
confidence: 96%
“…Animal models of obesity have been able to reveal similar findings and have shown additional cellular differences. After a brain lesion to the ventromedial nucleus of the hypothalamus (VMH) in laboratory rats, a method that produces obesity, intestinal cell hyperplasia and greater villi length occurs compared with the sham-lesion, lean animals 5 . Obese mouse models also show an increase in intestinal absorption 6 and permeability 7 .…”
Section: Introductionmentioning
confidence: 99%